Adolescent girls' sexual and reproductive health information needs and barriers in Cape Town - Natheerah Holtman; Million Bimerew; Katlego Mthimunye (AOSIS, 2024)
Background: The sexual and reproductive health (SRH) information needs of adolescent girls in developing countries are not being met. Aim: The study explored the sexual and reproductive health information needs, information-seeking behaviour and barriers among adolescent girls in the Western Cape, South Africa. Setting: The study was conducted in the South eastern sub district of Cape Town metropole. Methods: The study was conducted at one of the high schools in a highly populated area in the Cape Town metropole. Semi-structured interviews were conducted with 17 adolescent girls aged 16-17 years, who were recruited using purposive sampling techniques. The interviews were audio recorded and transcribed verbatim. Data were analysed using an inductive thematic analysis framework. Results: Three themes emerged from the data: (1) adolescent girls exhibit limited awareness and comprehension of sexual and reproductive health; (2) the information-seeking behaviours of adolescent girls regarding sexual and reproductive health and (3) barriers to seeking information. Conclusion: The establishment of primary healthcare facilities that are friendly to adolescents, combined with impactful reproductive health education and improved parent-adolescent girl relations, is crucial for promoting sexual and reproductive health among adolescent girls. Contribution: The study offered valuable insights into the SRH information needs, information-seeking behaviour and barriers faced by adolescent girls in accessing SRH information sources and services. These barriers include lack of knowledge about SRH and contraception, challenges within family dynamics, difficulties accessing friendly healthcare services and encountering negative attitudes from healthcare professionals.